Characterization of the LM5 pectic galactan epitope with synthetic analogues of β-1, 4-d-galactotetraose. (21st December 2016) - Andersen, Mathias C.F.; Boos, Irene; Marcus, Susan E.; Kračun, Stjepan K.; Rydahl, Maja Gro; Willats, William G.T.; Knox, J. Paul; Clausen, Mads H.
Abstract: Plant cell wall glycans are important polymers that are crucial to plant development and serve as an important source of sustainable biomass. The study of polysaccharides in the plant cell wall relies heavily on monoclonal antibodies (mAbs) for localization and visualization of glycans, using e.g. immunofluorescent microscopy. Here, we describe the detailed epitope mapping of the mAb LM5 that is shown to bind to a minimum of three sugar residues at the non-reducing end of linear beta-1, 4-linked galactan. The study uses de novo synthetic analogues of galactans combined with carbohydrate microarray and competitive inhibition ELISA for analysis of antibody-carbohydrate interactions. Graphical abstract: Highlights: The synthesis of three analogues of β-1, 4-D-galactotetraose. Efficient, mild methylation of Gal 4-OH with Meerwein's salt and Proton-sponge. Immobilization of oligosaccharides onto microarrays. Detailed epitope mapping of mAb LM5 using carbohydrate microarrays and ciELISA.